A press divided
1 online resource (xxv, 391 pages)
Keywords: "A Press Divided provides new insights regarding the sharp political divisions that existed among the newspapers of the Civil War era. These newspapers were divided between North and South, and also divided within the North and South. These divisions reflected and exacerbated the conflicts in political thought that caused the Civil War and the political and ideological battles within the Union and the Confederacy about how to pursue the war. In the North, dissenting voices alarmed the Lincoln administration to such a degree that draconian measures were taken to suppress dissenting newspapers and editors, while in the South, the Confederate government held to its fundamental belief in freedom of speech and was more tolerant of political attacks in the press. This volume consists of eighteen chapters on subjects including newspaper coverage of the rise of Lincoln, press reports on George Armstrong Custer, Confederate women war correspondents, Civil War photojournalists, newspaper coverage of the Emancipation Proclamation, and the suppression of the dissident press. This book tells the story of a divided press before and during the Civil War, discussing the roles played by newspapers in splitting the nation, newspaper coverage of the war, and the responses by the Union and Confederate administrations to press criticism."--Provided by publisher.